Neurological soft signs and their relationship to 1-year outcome in first-episode schizophrenia - Prikryl, Radovan; Ceskova, Eva; Kasparek, Tomas; Kucerova, Hana (European psychiatry, 2007)
OBJECTIVES: To examine the relationship between the severity of neurological soft signs at onset and at the 1-year follow-up of patients with schizophrenia, and to investigate temporal stability of neurological soft signs within 1year from the onset of the first episode schizophrenia. METHODS: The study included 92 first-episode male schizophrenic patients. Neurological soft signs were assessed on the Neurological Evaluation Scale (NES) during index hospitalization and at a 1-year follow-up. The patients were divided into remitters and non-remitters according to their psychiatric status assessed at the 1-year follow-up, using the Positive and Negative Syndrome Scale (PANSS). RESULTS: A trend for a lower score for the NES item "others" in late remitters versus non-remitters at baseline was found during index hospitalization. At the 1-year follow-up, the overall severity of the neurological soft signs was statistically significantly higher in non-remitters than in remitters. Within 1year after index hospitalization, a significant reduction of neurological soft signs, with the exception of sensory integration, occurred in remitters. Within 1year after index hospitalization, the non-remitters reported a significant reduction of the overall NES score. CONCLUSION: These findings in a population of patients with first episode schizophrenia are in accord with the findings of previous studies which found an association between neurological soft signs, treatment response and outcome. This association may characterize a subgroup of patients with a poor course of illness and outcome. Neurological soft signs might be regarded as one of the indicators of treatment outcome in patients suffering from their first episode of schizophrenia.
Keywords: Neurologic Examination; Schizophrenia; antipsychotika; Antipsychotic Agents; Male; neurologické vyšetření; Humans; Nervous System Diseases; prognóza; mužské pohlaví; dospělí; schizofrenie; lidé; Prognosis; Schizophrenic Psychology; hodnocení výsledků zdravotní péče; Psychiatric Status Rating Scales; schizofrenie (psychologie); Follow-Up Studies; nemoci nervového systému; Adult; následné studie; psychiatrické posuzovací škály; Outcome Assessment, Health Care